Mercury cycling between the water column and surface sediments in a contaminated area - Ramalhosa, Elsa (2006)
Mercury cycling in the water column and upper sediments of a contaminated area, the Largo do Laranjo, Aveiro (Portugal), was evaluated after determination of reactive and non-reactive mercury concentrations in the water column and pore waters of sediments, collected in several places of this bay. In the water column, reactive mercury concentrations varied between 10 and 37 pmol dm−3, the highest values being observed near the mercury anthropogenic source. However, reactive mercury was a narrowly constrained fraction of the total mercury, making up only 4–16% of the total, showing evidence of the importance of dissolved organic matter on mercury transport. In sediments, higher concentrations of mercury were also determined near industrial discharges. Results indicate the existence of an equilibrium between solid and liquid phases, determined by solid sediment/pore water distribution coefficients. Much of the mercury present in the solid fraction is associated with organic matter (r=0.837) and iron oxyhydroxides (r=0.919), but as oxides begin to dissolve in reduced sediments and organic matter decays, the adsorbed mercury is released. In fact, the mercury concentrations in pore waters of those contaminated sediments largely exceeded the values determined in the water column. As molecular diffusion may contribute to the dissolved mercury distribution in the overlying water column, this phenomenon was evaluated. However, the pore waters of Largo do Laranjo do not enrich the water column substantially in terms of reactive and non-reactive mercury. In fact, pore waters can contribute only to 0.2% and 0.5% of the reactive and non-reactive mercury present in the water column, respectively, showing that as long as mercury is being incorporated in sediments, it stays in stable forms.